2003
DOI: 10.1161/01.atv.0000067428.19031.28
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Remodeling and Stiffness in Patients With Pseudoxanthoma Elasticum

Abstract: Objective-Proteoglycans organize the extracellular matrix, act as signaling molecules, and are involved in cell migration and proliferation. They may play an important role in arterial geometric and elastic properties. The aim of the present study was to determine large artery phenotype in patients with pseudoxanthoma elasticum (PXE), a genetic disease characterized by proteoglycan accumulation and fragmented elastic fibers in connective tissues. Methods and Results-In 27 patients with PXE (25 females and 2 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 45 publications
3
37
4
Order By: Relevance
“…36 In addition, the presence of atherosclerotic plaques, which occur more frequently in PXE, is known to enhance stiffening of the arterial system. 37 Accordingly, we found a higher PWV in patients with PXE and carriers with PAD although this observation was not significant.In accordance with Boutouyrie et al 38 and Germain et al, 39 we observed no significant decrease in CDC between the different groups, but rather a tendency toward a slower decrease of CDC in function of age in patients (Figure 2). The latter has already been reported by Kornet et al 9 In carriers we observed a similar trend.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…36 In addition, the presence of atherosclerotic plaques, which occur more frequently in PXE, is known to enhance stiffening of the arterial system. 37 Accordingly, we found a higher PWV in patients with PXE and carriers with PAD although this observation was not significant.In accordance with Boutouyrie et al 38 and Germain et al, 39 we observed no significant decrease in CDC between the different groups, but rather a tendency toward a slower decrease of CDC in function of age in patients (Figure 2). The latter has already been reported by Kornet et al 9 In carriers we observed a similar trend.…”
supporting
confidence: 92%
“…In contrast, CDC measures stiffness at 1 point of the carotid artery. Further research is definitely warranted on the relation between alterations in wall composition and their relation to functional properties between the different parts of the arterial tree in patients with PXE.Carotid intima-media thickness was significantly increased in patients when compared with control subjects as also shown by Kornet et al 9 and Germain et al 39 Various mechanisms have been suggested to explain carotid wall thickening and thus higher carotid intima-media thickness in PXE subjects, including accelerated atherosclerosis, proteoglycan accumulation, and stimulation of vascular smooth muscle cell proliferation by increased proteoglycan content and elastin abnormalities.9,39 To our knowledge, there are no histological reports on vascular smooth muscle cell proliferation in patients with PXE. Our report is the first to show abnormal carotid intima-media thickness in carriers.…”
mentioning
confidence: 71%
“…The second major difference was in elastin density, which decreased selectively in old males. Previous studies also have observed either decreased 33 or no change 39,40 in elastin with age, but some studies have observed elastin fragmentation, 21 as we did in this study.…”
Section: Discussioncontrasting
confidence: 63%
“…Although this possibility has not been studied in detail, it is less likely because variations in the content of proteoglycans in the vascular wall do not correlate with changes in vascular stiffness. 39,41,42 Another important parameter that might account for changes in aortic stiffness with aging was addressed in prior studies from our laboratory on the endothelial dysfunction that accompanies aging. 12,43 Related to this, soy proteins have been implicated in vascular and endothelial protection.…”
Section: Discussionmentioning
confidence: 99%
“…function relationship of the arterial wall, and the effect on arterial stiffness of abnormal genetically determined wall components in particular. These diseases are complicated by major cardiovascular events, such as dilatation, dissection, and rupture (Marfan syndrome, Ehlers-Danlos syndrome) or hypertrophy and stenosis (Williams syndrome, pseudoxanthoma elasticum 38,39 ).…”
Section: Monogenic Disease and Related Knockout Micementioning
confidence: 99%